Lung Ultrasound in Critically Ill Patients - Silva, Ana; Marques, Joana; Pais Martins, António (Journal of the Portuguese Society of Anesthesiology, 2014)
The pulmonary evaluation of critically ill patients has been traditionally performed with the use of chest radiography and computed tomography, however increasingly ultrasound has been shown to be a useful diagnostic method. For being a non-invasive technique with low cost, that does not use radiation and can be repeated without additional risk, it had became a very attractive technique to be performed at the bedside. In this review we explain the lung ultrasound technique, define the normal pattern, the artifacts and the criteria for the main disease.